Definições de bronquiolite aguda e eficácia de Azitromicina para prevenção de sibilância recorrente - Roza, Clarissa Aires (2016)
Introduction: Acute bronchiolitis (AB) is the most common disease of the lower airways in infants. There is disagreement in the literature on the AB definition, especially in relation to age and recurrence of symptoms. As some children may develop post-bronchiolitis recurrent wheezing, it has been widely studied interventions to prevent recurrence wheezing. Methods: A systematic literature review was conducted in MEDLINE with filter for "clinical trial" and the search term was "acute bronchiolitis”. It was established two distinct groups of setting: 1-first episode of wheezing and 2-clinical presentation of AB below 24 months of age, regardless of recurrence. Furthermore, we conducted a double-blind randomized placebo-controlled trial with patients admitted for AB to test the hypothesis that use of azithromycin in the acute episode of AB may reduce the risk of recurrent wheezing. Results: The systematic review included 79 trials and showed that the majority (59.49%) defines AB as the first episode of wheezing in infants and 56.96% includes children under 12 months. The trial included 91 patients (51 in the azithromycin group and 40 in the placebo group). The risk of hospital readmission was not different between the groups studied 1, 3 and 6 months after AB. The risk of recurrent wheezing was significantly reduced up to 6 months after admission for AB (p = 0.022). Conclusion: AB definition used by most clinical trials was the first episodes of wheezing in children, and most of the studies included patients up to 12 months. Therefore, this should be the definition used in guidelines and documents ofrecommendations. The use of azithromycin in the first episode of AB reduces the risk of recurrent wheezing in infants.